2022
DOI: 10.1002/ijgo.14375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intimate partner violence in pregnancy on maternal and perinatal outcomes at the Korle Bu teaching hospital, Ghana: An observational cross sectional study

Abstract: Objective: To determine the association between intimate partner violence and pregnancy outcomes. Methods:This was a descriptive study of sociodemographic characteristics of participants, their partners and intimate partner violence. Participants' delivery records were reviewed for additional medical and obstetric information and abused women and their neonates followed until discharge. χ 2 and Student t test were used to assess associations, followed by logistic regression with odds ratio (OR) and 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Our search identified 2418 unique titles and 30 studies met inclusion criteria (Supporting Information S2: Figure S1 for PRISMA flow diagram; n = 280 864, Supporting Information S1: Table S1). 15,16,23–50 The majority of studies were prospective cohort studies ( n = 17); there were six prospective cross‐sectional studies, three retrospective studies, two case control studies, one study described as “comparative,” and one study described as “prospective descriptive longitudinal study.” Included studies were conducted in 19 different countries with 12 (40%) completed in Asia, 6 (20%) conducted in Africa as well as Europe, 5 (17%) in North America, and 1 (0.3%) in South America. 12 (40%) of studies were multi‐centre.…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 2418 unique titles and 30 studies met inclusion criteria (Supporting Information S2: Figure S1 for PRISMA flow diagram; n = 280 864, Supporting Information S1: Table S1). 15,16,23–50 The majority of studies were prospective cohort studies ( n = 17); there were six prospective cross‐sectional studies, three retrospective studies, two case control studies, one study described as “comparative,” and one study described as “prospective descriptive longitudinal study.” Included studies were conducted in 19 different countries with 12 (40%) completed in Asia, 6 (20%) conducted in Africa as well as Europe, 5 (17%) in North America, and 1 (0.3%) in South America. 12 (40%) of studies were multi‐centre.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, we noticed higher reported rates of sexual and emotional violence in the postpartum period among participants in the Group ANC intervention. This could be related to elevated rates of IPV that have been reported among Ghanaian women during pregnancy [ 3 ], or it could indicate a better understanding by the women enrolled in Group ANC of the different and often less recognised forms of IPV (e.g. sexual and emotional).…”
Section: Discussionmentioning
confidence: 99%
“…Alangea and colleagues explored rates of IPV among a population-based sample of 2000 reproductive-age women and found that the rates over the last year were 24.6% for emotional violence, 15.5% for physical violence, and 11.8% for sexual violence [ 2 ]. During the reproductive age, particularly during pregnancy, IPV can lead to detrimental outcomes for both the mother and the foetus, including gestational hypertension, low birth weight, foetal distress, and maternal death [ 3 ]. Researchers have identified IPV as a barrier in accessing and utilising antenatal care (ANC) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%